Vloga elektroporacije zdravil za napredno zdravljenje - Kandušer, Maša (Farmacevtski vestnik, 2024)
Advances in biomedicine enhanced the development of advanced therapy medicinal products for gene, cell and tissue therapy, based on recombinant gene delivery, modified somatic cells or are used for restoring, replacing or regenerating of tissues. Electroporation is suitable to prepare products for advanced therapies. Electroporation is achieved when we expose cells to short, high-voltage electric pulses that cause temporary, reversible, or permanent, irreversible permeabilization of the cell membrane. Reversible electroporation is used for electrochemotheraphy, gene electrotransfection and for electrofusion. Irreversible electroporation is used for non-thermal tissue ablation and for extraction of the cellular contents. For successful use of electroporation, we need to understand the mechanisms and parameters that affect the outcome. For the development of advance therapy medicinal products reversible electroporation can be used for gene, cell and tissue therapy and for cell vaccines based on immuno-hybridoma. Irreversible electroporation is suitable for the preparation of biocompatible supports in tissue therapy.
Keywords: elektrofuzija; elektrogenska transfekcija; Elektroporacija; zdravila za napredno zdravljenje